Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
The first thief takes (1/2 x + 1) . What remains ? x - (1/2x + 1)
So the 2nd thief takes 2/3 of [ x - (1/2x + 1) ]
What remains ? x - 2/3 [ x - (1/2x + 1) ]
So the 3rd thief takes 2/3 of { x - 2/3 [ x - (1/2x + 1) ] } and he takes 1 more .
What remains ? x - ( 2/3 { x - 2/3 [ x - (1/2x + 1) ] } + 1 )
And that whole ugly thing is equal to ' 1 ', so you can solve it for 'x'..
The whole problem from here on is an exercise in simplifying
an expression with a bunch of 'nested' parentheses in it.
===============================================
This is a lot harder than just solving the problem with logic and
waving your hands in the air. Here's how you would do that:
Start from the end and work backwards:
-- One diamond is left.
-- Before the 3rd thief took 1 more, there were 2.
-- That was 1/3 of what was there before the 3rd man took 2/3.
So he found 6 when he arrived.
-- 6 was 1/3 of what was there before the second thief helped himself.
So there were 18 when the 2nd man arrived.
-- 18 was 1 less than what was there before the first thief took 1 extra.
So he took his 1 extra from 19.
-- 19 was the remaining after the first man took 1/2 of all on the table.
So there were 38 on the table when he arrived.
Thank you for your generous 5 points.
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.